An overview of weighted goal programming: a multi-objective transportation problem with some fresh viewpoints - Gütmen, Selma; Roy, Sankar Kumar; Weber, Gerhard-Wilhelm (Central European journal of operations research, 2024)
Goal programming (GP) is one of the widely used and effective method of solving real-world multi-objective decision-making problems. The term “multi-objective transportation problem” (MOTP) covers a specific class of vector maximum (minimum) linear programming problem that typically has multiple, competing, and incompatible objective functions. In this article, GP and weighted goal programming (WGP) are summarized in MOTP. Furthermore, its advantages over GP are illustrated by a theorem. Additionally, by utilizing WGP, a solution procedure is articulated for MOTP. Finally, an application on screen-panels of mobile devices is presented to explore the applicability. The paper ends with a conclusion and including an outlook to future studies, whereby we address internal and external transportation, and view the internal one with a broader understanding of logistics.